Carbon fiber-based electrically conductive concrete for salt-free deicing of pavements. (1st December 2018) - Sassani, Alireza; Arabzadeh, Ali; Ceylan, Halil; Kim, Sunghwan; Sadati, S.M. Sajed; Gopalakrishnan, Kasthurirangan; Taylor, Peter C.; Abdualla, Hesham
Abstract: Traditional methods of removing snow/ice from pavements involve application of deicing salts and mechanical removal that carry environmental concerns. In this study, the feasibility of applying carbon fiber-based electrically conductive concrete (ECON) in heated pavement systems (HPS) as an alternative to traditional methods was investigated. Optimum carbon fiber dosage to achieve desirable electrical conductivity and avoid excessive fiber use was determined by studying carbon fiber percolation in different cementitious composites. System design was evaluated by finite element (FE) analysis. Heating performance in terms of energy consumption regime was studied by quasi-long-term (460-day) experimental study using a prototype ECON slab. Percolation transition zone of carbon fiber in paste, mortar, and concrete were respectively 0.25–1% (Vol.), 0.6–1% (Vol.), and 0.5–0.75% (Vol.). Optimum fiber dosage in ECON with respect to conductivity was 0.75%, resulting in volume conductivity of 1.86 × 10 −2 (S/cm) at 28 days and 1.22 × 10 −2 (S/cm) at 460 days of age. Electrical-energy-to-heat-energy conversion efficiency decreased from 66% at 28 days to 50% at 460-day age. The results showed that the studied technology could be effectively applied for ice/snow melting on pavement surfaces and provide a feasible alternative to traditional methods if the ECON mixing proportions and system configurations are made with necessary precautions. Highlights: Optimum carbon fiber content in electrically conductive portland cement concrete (ECON) is age-dependent. Electrical conductivity of ECON decreases dramatically with age up to 150 days. The service life of an ECON heated pavement depends on the initial value and the growth rate of conductivity. ECON can be effectively used to melt ice/snow on pavements with acceptable energy demand. The performance of an ECON heated pavement system can be evaluated by finite element (FE) modeling.